The effects of an imposed performance strategy upon subjective mental workload. - Finucci, Helen Louise. (My University, 1990)
Increasingly complex technology in modern times has changed the nature of many work activities. Mechanisation and automation have served to emphasise the importance of mental workload to productivity, physicaI and mental health. The study uses a simulated routine office stocktaking task to compare subjective experiences of mental workload between traditional pen and paper methods and the more recently developed computer techniques. An analysis is also made of assessments of difficulty by subjects free to adopt a working method of their choice (ie. in a flexible environment) and subjects whohave no freedom of working method (ie. a rigid externally imposed working strategy). Also included is an analysis of the cognitive strategies adopted during task performance and across the different t.reatmerrt conditions. Research findings are of particular relevance to the design of jobs in the modern office environment where human-computer interaction is becoming increasingly prevalent, the effective design of man-machine systems, and to the general field of workload research.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, for the Degree of Master of Arts.
Keywords: Mental work.; Work -- Psychological aspects.; Human-computer interaction.